A closed pore enriched in-situ gas assisted pore-forming and doped hard carbon negative electrode material and a preparation method thereof
Patent Information
- Application Number
- CN202611453622.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-18
- Publication Date
- 2026-10-23
AI Technical Summary
[0004]本发明的目的在于解决现有硬碳负极材料孔结构调控与杂原子掺杂难以协同、低电位平台储钠性能不佳等技术问题,提供一种闭孔富集型原位气体辅助造孔并掺杂的硬碳负极材料及其制备方法
1、本发明利用掺杂添加剂在热解过程中原位释放气体,同时提供异质元素,实现孔结构生成与元素掺杂的一体化,实现造孔与掺杂同步调控。
Smart Images

Figure CN122957822A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of hard carbon anode material technology, specifically to a closed-pore enrichment type in-situ gas-assisted pore formation and doping hard carbon anode material and its preparation method. Background Technology
[0002] Lithium-ion batteries, with their high energy density and mature industrial chain, have been widely used in portable electronic devices, electric transportation, and energy storage systems. However, the limited reserves and uneven regional distribution of lithium resources, along with significant fluctuations in raw material prices, restrict their further application in large-scale, low-cost energy storage. Sodium-ion batteries, due to abundant sodium resources, lower costs, and a similar working principle to lithium-ion batteries, are considered one of the important technological routes for large-scale energy storage and low-cost battery applications. In sodium-ion battery systems, the anode material is a key component determining the battery's energy density, rate performance, cycle life, and safety. Hard carbon materials, with their disordered carbon layer structure, large interlayer spacing, and abundant pore structure, exhibit lower sodium-ion intercalation potential, and their readily available raw materials and easily controllable costs, demonstrating outstanding comprehensive advantages in sodium storage within sodium-ion battery anode material systems.
[0003] Currently, existing structural control technologies for hard carbon anode materials mainly include activation-based pore formation and heteroelement doping. Activation methods are commonly used to construct porous hard carbon, forming well-developed open-pore structures through activating agents or activating gases (such as KOH, CO2, NH3, water vapor, etc.), which can subsequently form closed-pore structures during carbonization. Heteroelement doping introduces elements such as nitrogen, oxygen, sulfur, phosphorus, and boron by adding dopants (such as urea, melamine, boric acid, etc.) to adjust the electronic structure, defect types, interlayer spacing, and sodium affinity of the carbon material. Although these technologies are widely used, they still have significant shortcomings. These technologies mostly rely on a single mechanism to improve the sodium storage performance of hard carbon materials, mainly by increasing open pores, defects, or surface functional groups to improve capacity. This easily leads to problems such as increased electrolyte side reactions, decreased initial coulombic efficiency, excessively high slope capacity ratio, and insufficient low-potential plateau capacity, making it difficult to achieve both high capacity and high efficiency. In addition, existing gas pore-forming or heterogeneous element doping technologies usually focus on increasing active sites or improving electronic conductivity, often using additives only as foaming agents, activators or doping sources. They fail to fully utilize the combined relationship between the "gas release temperature window, precursor pyrolysis / carbonization window, and carbon framework rearrangement sealing window", and cannot directionally construct internal pore, semi-closed pore or closed pore structures suitable for low-potential sodium storage, making it difficult to selectively improve the capacity of low-potential platforms. Summary of the Invention
[0004] The purpose of this invention is to solve the technical problems of existing hard carbon anode materials, such as the difficulty in coordinating pore structure control and heteroatom doping, and poor sodium storage performance at low potential plateaus. This invention provides a closed-pore enriched in-situ gas-assisted pore-forming and doped hard carbon anode material and its preparation method. This invention relies on the in-situ pyrolysis of dopant additives to generate a large amount of gas, which can form closed-pore and semi-closed-pore structures composed of micropores and ultramicropores within the hard carbon anode material. The heterogeneous elements introduced by the doping can be embedded in the carbon framework or form functional groups on the surface and edges of the carbon material, thus obtaining a closed-pore enriched in-situ gas-assisted pore-forming and doped hard carbon anode material.
[0005] The above-mentioned objective of this invention is achieved through the following technical solution: The first aspect of this invention provides a method for preparing a hard carbon anode material, comprising the following steps: S1. Hard carbon precursor powder is obtained by crushing, sieving, washing and drying the hard carbon precursor. The hard carbon precursor powder is pre-carbonized at 200-400 °C and then acid-washed to remove impurities to obtain pre-treated hard carbon precursor. S2. The pretreated hard carbon precursor obtained in step S1 is uniformly mixed with the doping additive to obtain a composite precursor; the doping additive is selected from one or more of urea, thiourea, ammonium borate, ammonium phosphate, melamine, dicyandiamide, cyanamide, ammonium oxalate, ammonium bicarbonate, amino acids and chitosan. S3. Under an inert atmosphere, the composite precursor obtained in step S2 is first heat-treated at 200-400 °C to allow the doped additives to release gases through thermal decomposition, and then carbonized at 800-1600 °C to obtain the hard carbon anode material.
[0006] This invention combines a hard carbon precursor with a dopant additive that can release gases through thermal decomposition and provide heterogeneous elements. The additive releases gases in situ during the carbonization stage of the precursor, inducing the formation of micropores, ultramicropores, or internal nanopores. Simultaneously, heterogeneous elements such as nitrogen, oxygen, sulfur, phosphorus, and boron are incorporated into the carbon framework or retained as specific functional structures. Subsequently, high-temperature carbonization promotes carbon layer shrinkage, rearrangement, and partial pore closure, constructing a closed-pore or semi-closed-pore enriched structure. This selectively improves the low-potential plateau capacity of the sodium-ion battery anode material, ultimately obtaining a high-capacity hard carbon anode material with a high plateau ratio.
[0007] Furthermore, in step S1, the hard carbon precursor is selected from one or more of the following: corn cob, coconut shell, bamboo powder, rice husk, walnut shell, waste tea leaves, coffee grounds, apple peel, banana peel, lignin, cellulose, starch, glucose, sucrose, and fructose. The synergistic regulation mechanism of this invention is applicable to various biomass hard carbon precursors such as corn cob, coconut shell, and bamboo powder, thus broadening the range of raw material selection.
[0008] Further, in step S1, the specific operation of the pre-carbonization treatment is as follows: the hard carbon precursor powder is placed in a tube furnace and heated to 200-400 ℃ at a heating rate of 5-10 ℃ / min under an inert atmosphere, and held at that temperature for 1-48 h for pre-carbonization treatment.
[0009] Further, in step S1, the acid washing and impurity removal treatment uses one or more of hydrochloric acid (HCl), nitric acid (HNO3), hydrofluoric acid (HF), sulfuric acid (H2SO4), oxalic acid, and citric acid.
[0010] Furthermore, in step S1, the acid washing and impurity removal treatment takes 1-12 hours.
[0011] Furthermore, in step S1, the temperature of the acid washing and impurity removal treatment is 75-85 ℃.
[0012] Further, in step S2, the mass ratio of the pretreated hard carbon precursor to the doped additive is 1:(1-10).
[0013] Furthermore, in step S2, the mixing method is grinding or ball milling.
[0014] Furthermore, the ball-to-material ratio in the ball milling mixture is (8-12):1, the ball milling speed is 250-350 r / min, and the ball milling time is 3-5 h.
[0015] Furthermore, the ball milling and mixing uses an organic solvent as the dispersion medium, and the organic solvent is ethanol; the ball milling and mixing process further includes a step of drying at 50-70 °C to remove the organic solvent.
[0016] Furthermore, in step S3, the heat treatment time is 1-48 h.
[0017] Furthermore, in step S3, the carbonization treatment time is 1-48 h.
[0018] Further, in step S3, the composite precursor is placed in a tube furnace and heated to 200-400 °C at a heating rate of 1-5 °C / min under an inert atmosphere, and held at this temperature for 1-5 h for heat treatment. Subsequently, it is heated to 800-1600 °C at a heating rate of 5-10 °C / min and held at this temperature for 1-48 h for carbonization treatment. Within the temperature range of 200-400 °C, the hard carbon precursor undergoes dehydration, condensation, cross-linking, and preliminary aromatization reactions sequentially, gradually constructing an initial carbon framework with certain mechanical stability. Simultaneously, the additives, which combine gas generation and doping functions, gradually decompose and activate within this temperature window. Combined with a slow heating process, this achieves stable and gradual gas release, effectively avoiding problems such as excessive foaming, pore structure collapse, and particle breakage caused by rapid and violent decomposition of the additives. Gas can escape uniformly inside the composite precursor, inducing the formation of uniformly distributed micropores, ultramicropores, or initial internal pore structures, providing a structural basis for subsequently improving the low-potential platform sodium storage capacity of hard carbon anode materials.
[0019] Furthermore, the inert atmosphere is maintained at 70-90 mL / min. -1 flow into the tube furnace.
[0020] The second aspect of the present invention provides a hard carbon anode material prepared by the preparation method described in the first aspect.
[0021] The third aspect of this invention provides an application of the hard carbon anode material described in the second aspect in a sodium-ion battery.
[0022] The above-described technical solution of the present invention has the following beneficial effects: 1. This invention utilizes the in-situ release of gas by doping additives during pyrolysis, while simultaneously providing heterogeneous elements, to achieve the integration of pore structure generation and element doping, and to realize the synchronous control of pore formation and doping.
[0023] 2. The hard carbon anode material prepared in this invention, through the matching of the gas release stage and the high-temperature carbon layer rearrangement stage, first forms internal micropores and ultramicropores, and then forms closed-pore or semi-closed-pore structures through high-temperature shrinkage and pore closure. This is beneficial for sodium storage at low potential plateaus and selectively improves plateau capacity. The heterogeneous elements in the doping additives introduce carbon frameworks or form surface and edge functional group structures, widening the carbon layer spacing to meet the sodium ion insertion / extraction requirements. The synergistic effect of these two factors enables the reversible sodium storage capacity of the hard carbon anode material to be ≥340 mAh·g. -1 The platform capacity accounts for ≥70%, and its sodium storage performance is significantly better than that of traditional modified hard carbon materials.
[0024] 3. The preparation method of the present invention does not require complex equipment, has mild reaction conditions, low raw material costs, and can achieve large-scale production, providing a feasible path for the large-scale preparation of high-performance sodium-ion battery hard carbon anode materials. Attached Figure Description
[0025] Figure 1 Small-angle X-ray scattering (SAXS) intensity diagrams of the hard carbon anode materials prepared in Example 1 and Comparative Example 1.
[0026] Figure 2 The image shows the X-ray photoelectron spectroscopy (XPS) spectra of the hard carbon anode materials prepared in Example 1 and Comparative Example 1.
[0027] Figure 3 The charge-discharge curves of a sodium-ion half-cell assembled using the hard carbon anode material prepared in Example 1. Detailed Implementation
[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0029] The present invention will be further described below with reference to the accompanying drawings and specific embodiments, so that those skilled in the art can better understand and implement the present invention. However, the embodiments described are not intended to limit the present invention.
[0030] Unless otherwise specified, the experimental methods used in the following examples are conventional methods, and the materials and reagents used are commercially available.
[0031] Example 1 (using corn cob as hard carbon precursor and urea as dopant additive) A method for preparing a hard carbon anode material includes the following steps: S1. Hard Carbon Precursor Treatment: After removing mud, sand, outer skin, and visible impurities from the corn cob raw material, it is cut into small pieces and crushed in a pulverizer to obtain coarse corn cob powder. The coarse corn cob powder is sieved through a standard sieve to collect corn cob powder with a particle size of 200 mesh. The sieved corn cob powder is repeatedly washed with deionized water until the washing liquid is clear to remove surface dust and water-soluble impurities. Subsequently, the washed corn cob powder is filtered and dried in an oven at 80 ℃ to obtain pre-treated corn cob powder. 20 g of the pre-treated corn cob powder is weighed and placed in a tube furnace. Under an inert atmosphere, the temperature is increased to 300 ℃ at 8 ℃ / min and held for 3 h for pre-carbonization treatment to obtain pre-carbonized corn cob carbon powder. The pre-carbonized corn cob carbon powder is placed in a mixed acid of 3 mol / L HCl and 5 wt% HF and stirred at 80 ℃ for 12 h to remove silicon impurities and metal ion impurities. The mixture was then washed with deionized water until neutral and dried to obtain black pretreated corn cob toner.
[0032] S2. Additive compounding: Weigh 1 g of pretreated corn cob carbon powder and 3 g of urea, place them in the zirconia ball mill jar of a planetary ball mill, add 30 mL of anhydrous ethanol as the dispersion medium, set the ball-to-material ratio to 10:1, and the ball milling speed to 300 r·min. -1 The mixture was continuously ball-milled for 4 hours to obtain a uniform slurry. The slurry was then poured into an evaporating dish and dried in a 60 °C oven for 12 hours to completely remove anhydrous ethanol, yielding a black powdery composite precursor.
[0033] S3. Carbonization treatment: The black powdered composite precursor is placed in a tube furnace, and argon gas is introduced as a protective atmosphere (gas flow rate 80 mL / min). -1 First, the temperature is increased to 300 ℃ at a heating rate of 3 ℃ / min and held for 1 h for heat treatment. Then, the temperature is increased to 1300 ℃ at a heating rate of 8 ℃ / min and held for 3 h for carbonization treatment. After natural cooling to room temperature, the material is taken out and ground into powder to obtain hard carbon anode material.
[0034] Example 2 (using corn cob as hard carbon precursor and thiourea as dopant additive) A method for preparing a hard carbon anode material includes the following steps: S1. Hard Carbon Precursor Treatment: After removing mud, sand, outer skin, and visible impurities from the corn cob raw material, it is cut into small pieces and crushed in a pulverizer to obtain coarse corn cob powder. The coarse corn cob powder is sieved through a standard sieve to collect corn cob powder with a particle size of 200 mesh. The sieved corn cob powder is repeatedly washed with deionized water until the washing liquid is clear to remove surface dust and water-soluble impurities. Subsequently, the washed corn cob powder is filtered and dried in an oven at 80 ℃ to obtain pre-treated corn cob powder. 20 g of the pre-treated corn cob powder is weighed and placed in a tube furnace. Under an inert atmosphere, the temperature is increased to 300 ℃ at 8 ℃ / min and held for 3 h for pre-carbonization treatment to obtain pre-carbonized corn cob carbon powder. The obtained pre-carbonized corn cob carbon powder is placed in a mixed acid of 3 mol / L HCl and 5 wt% HF and stirred at 80 ℃ for 12 h to remove silicon impurities and metal ion impurities. The mixture was then washed with deionized water until neutral and dried to obtain black pretreated corn cob toner.
[0035] S2. Additive Combination: Weigh 1 g of pretreated corn cob carbon powder and 3 g of thiourea, place them in the zirconia ball mill jar of a planetary ball mill, add 30 mL of anhydrous ethanol as the dispersion medium, set the ball-to-material ratio to 10:1, and the ball milling speed to 300 r·min. -1The mixture was continuously ball-milled for 4 hours to obtain a uniform slurry. The slurry was then poured into an evaporating dish and dried in a 60 °C oven for 12 hours to completely remove anhydrous ethanol, yielding a black powdery composite precursor.
[0036] S3. Carbonization treatment: The black powdered composite precursor is placed in a tube furnace, and argon gas is introduced as a protective atmosphere (gas flow rate 80 mL / min). -1 First, the temperature is increased to 300 ℃ at a heating rate of 3 ℃ / min and held for 1 h for heat treatment. Then, the temperature is increased to 1300 ℃ at a heating rate of 8 ℃ / min and held for 3 h for carbonization treatment. After natural cooling to room temperature, the material is taken out and ground into powder to obtain hard carbon anode material.
[0037] Example 3 (using corn cob as hard carbon precursor and ammonium borate as dopant additive) A method for preparing a hard carbon anode material includes the following steps: S1. Hard Carbon Precursor Treatment: After removing mud, sand, outer skin, and visible impurities from the corn cob raw material, it is cut into small pieces and crushed in a pulverizer to obtain coarse corn cob powder. The coarse corn cob powder is sieved through a standard sieve to collect corn cob powder with a particle size of 200 mesh. The sieved corn cob powder is repeatedly washed with deionized water until the washing liquid is clear to remove surface dust and water-soluble impurities. Subsequently, the washed corn cob powder is filtered and dried in an oven at 80 ℃ to obtain pre-treated corn cob powder. 20 g of the pre-treated corn cob powder is weighed and placed in a tube furnace. Under an inert atmosphere, the temperature is increased to 300 ℃ at 8 ℃ / min and held for 3 h for pre-carbonization treatment to obtain pre-carbonized corn cob carbon powder. The obtained pre-carbonized corn cob carbon powder is placed in a mixed acid of 3 mol / L HCl and 5 wt% HF and stirred at 80 ℃ for 12 h to remove silicon impurities and metal ion impurities. The mixture was then washed with deionized water until neutral and dried to obtain black pretreated corn cob toner.
[0038] S2. Additive Combination: Weigh 1 g of black pretreated corn cob carbon powder and 3 g of ammonium borate, place them in the zirconia ball mill jar of a planetary ball mill, add 30 mL of anhydrous ethanol as the dispersion medium, set the ball-to-material ratio to 10:1, and the ball milling speed to 300 r·min. -1 The mixture was continuously ball-milled for 4 hours to obtain a uniform slurry. The slurry was then poured into an evaporating dish and dried in a 60 °C oven for 12 hours to completely remove anhydrous ethanol, yielding a black powdery composite precursor.
[0039] S3. Carbonization treatment: The black powdered composite precursor is placed in a tube furnace, and argon gas is introduced as a protective atmosphere (gas flow rate 80 mL / min). -1First, the temperature is increased to 300 ℃ at a heating rate of 3 ℃ / min and held for 1 h for heat treatment. Then, the temperature is increased to 1300 ℃ at a heating rate of 8 ℃ / min and held for 3 h for carbonization treatment. After natural cooling to room temperature, the material is taken out and ground into powder to obtain hard carbon anode material.
[0040] Example 4 (using coconut shell as hard carbon precursor and urea as dopant additive) A method for preparing a hard carbon anode material includes the following steps: S1. Hard Carbon Precursor Treatment: After removing mud, sand, outer skin, and visible impurities from the coconut shell raw material, it is cut into small pieces and crushed in a pulverizer to obtain coarse coconut shell powder. The coarse coconut shell powder is sieved through a standard sieve to collect coconut shell powder with a particle size of 200 mesh. The sieved coconut shell powder is repeatedly washed with deionized water until the washing liquid is clear to remove surface dust and water-soluble impurities. Subsequently, the washed coconut shell powder is filtered and dried in an oven at 80 ℃ to obtain pre-treated coconut shell powder. 20 g of the pre-treated coconut shell powder is weighed and placed in a tube furnace. Under an inert atmosphere, the temperature is increased to 300 ℃ at 8 ℃ / min and held for 3 h for pre-carbonization treatment to obtain pre-carbonized coconut shell carbon powder. The obtained pre-carbonized coconut shell carbon powder is placed in a mixed acid of 3 mol / L HCl and 5 wt% HF and stirred at 80 ℃ for 12 h to remove silicon impurities and metal ion impurities. It was then washed with deionized water until neutral and dried to obtain black pretreated coconut shell carbon powder.
[0041] S2. Additive compounding: Weigh 1 g of black pretreated coconut shell carbon powder and 3 g of urea, place them in the zirconia ball mill jar of a planetary ball mill, add 30 mL of anhydrous ethanol as the dispersion medium, set the ball-to-material ratio to 10:1, and the ball milling speed to 300 r·min. -1 The mixture was continuously ball-milled for 4 hours to obtain a uniform slurry. The slurry was then poured into an evaporating dish and dried in a 60 °C oven for 12 hours to completely remove anhydrous ethanol, yielding a black powdery composite precursor.
[0042] S3. Carbonization treatment: The black powdered composite precursor is placed in a tube furnace, and argon gas is introduced as a protective atmosphere (gas flow rate 80 mL / min). -1 First, the temperature is increased to 300 ℃ at a heating rate of 3 ℃ / min and held for 1 h for heat treatment. Then, the temperature is increased to 1300 ℃ at a heating rate of 8 ℃ / min and held for 3 h for carbonization treatment. After natural cooling to room temperature, the material is taken out and ground into powder to obtain the hard carbon anode material.
[0043] Example 5 (using bamboo powder as hard carbon precursor and urea as dopant additive) A method for preparing a hard carbon anode material includes the following steps: S1. Hard Carbon Precursor Treatment: After removing mud, sand, outer skin, and visible impurities from the bamboo powder raw material, it is cut into small pieces and crushed in a pulverizer to obtain coarse bamboo powder. The coarse bamboo powder is sieved through a standard sieve to collect bamboo powder with a particle size of 200 mesh. The sieved bamboo powder is repeatedly washed with deionized water until the washing liquid is clear to remove surface dust and water-soluble impurities. Subsequently, the washed bamboo powder is filtered and dried in an oven at 80 ℃ to obtain pretreated bamboo powder. 20 g of the pretreated bamboo powder is weighed and placed in a tube furnace. Under an inert atmosphere, the temperature is increased to 300 ℃ at 8 ℃ / min and held for 3 h for pre-carbonization treatment to obtain pre-carbonized bamboo powder. The obtained pre-carbonized bamboo powder is placed in a mixed acid of 3 mol / L HCl and 5 wt% HF and stirred at 80 ℃ for 12 h to remove silicon impurities and metal ion impurities. It was then washed with deionized water until neutral and dried to obtain black pretreated bamboo powder carbon powder.
[0044] S2. Additive compounding: Weigh 1 g of black pretreated bamboo powder and 3 g of urea, place them in the zirconia ball mill jar of a planetary ball mill, add 30 mL of anhydrous ethanol as the dispersion medium, set the ball-to-material ratio to 10:1, and the ball milling speed to 300 r·min. -1 The mixture was continuously ball-milled for 4 hours to obtain a uniform slurry. The slurry was then poured into an evaporating dish and dried in a 60 °C oven for 12 hours to completely remove anhydrous ethanol, yielding a black powdery composite precursor.
[0045] S3. Carbonization treatment: The black powdered composite precursor is placed in a tube furnace, and argon gas is introduced as a protective atmosphere (gas flow rate 80 mL / min). -1 First, the temperature is increased to 300 ℃ at a heating rate of 3 ℃ / min and held for 1 h for heat treatment. Then, the temperature is increased to 1300 ℃ at a heating rate of 8 ℃ / min and held for 3 h for carbonization treatment. After natural cooling to room temperature, the material is taken out and ground into powder to obtain hard carbon anode material.
[0046] Comparative Example 1 (using corn cob as hard carbon precursor, without any additives) A method for preparing a hard carbon anode material includes the following steps: S1. Hard Carbon Precursor Treatment: After removing mud, sand, outer skin, and visible impurities from the corn cob raw material, it is cut into small pieces and crushed in a pulverizer to obtain coarse corn cob powder. The coarse corn cob powder is sieved through a standard sieve to collect corn cob powder with a particle size of 200 mesh. The sieved corn cob powder is repeatedly washed with deionized water until the washing liquid is clear to remove surface dust and water-soluble impurities. Subsequently, the washed corn cob powder is filtered and dried in an oven at 80 ℃ to obtain pre-treated corn cob powder. 20 g of the pre-treated corn cob powder is weighed and placed in a tube furnace. Under an inert atmosphere, the temperature is increased to 300 ℃ at 8 ℃ / min and held for 3 h for pre-carbonization treatment to obtain pre-carbonized corn cob carbon powder. The obtained pre-carbonized corn cob carbon powder is placed in a mixed acid of 3 mol / L HCl and 5 wt% HF and stirred at 80 ℃ for 12 h to remove silicon impurities and metal ion impurities. The mixture was then washed with deionized water until neutral and dried to obtain black pretreated corn cob toner.
[0047] S2. Carbonization treatment: The pretreated black corn cob carbon powder is placed in a tube furnace, and argon gas is introduced as a protective atmosphere (gas flow rate 80 mL / min). -1 First, the temperature is increased to 300 ℃ at a heating rate of 3 ℃ / min and held for 1 h. Then, the temperature is increased to 1300 ℃ at a heating rate of 8 ℃ / min and held for 3 h. After natural cooling to room temperature, the material is removed and ground into powder to obtain hard carbon anode material.
[0048] Comparative Example 2 (using corn cob as hard carbon precursor and urea as dopant additive). A method for preparing a hard carbon anode material includes the following steps: S1. Hard Carbon Precursor Treatment: After removing mud, sand, outer skin, and visible impurities from the corn cob raw material, it is cut into small pieces and crushed in a pulverizer to obtain coarse corn cob powder. The coarse corn cob powder is sieved through a standard sieve to collect corn cob powder with a particle size of 200 mesh. The sieved corn cob powder is repeatedly washed with deionized water until the washing liquid is clear to remove surface dust and water-soluble impurities. Subsequently, the washed corn cob powder is filtered and dried in an oven at 80 ℃ to obtain pre-treated corn cob powder. 20 g of the pre-treated corn cob powder is weighed and placed in a tube furnace. Under an inert atmosphere, the temperature is increased to 300 ℃ at 8 ℃ / min and held for 3 h for pre-carbonization treatment to obtain pre-carbonized corn cob carbon powder. The obtained pre-carbonized corn cob carbon powder is placed in a mixed acid of 3 mol / L HCl and 5 wt% HF and stirred at 80 ℃ for 12 h to remove silicon impurities and metal ion impurities. The mixture was then washed with deionized water until neutral and dried to obtain black pretreated corn cob toner.
[0049] S2. Carbonization treatment: The pretreated black corn cob carbon powder is placed in a tube furnace, and argon gas is introduced as a protective atmosphere (gas flow rate 80 mL / min). -1 First, the temperature is raised to 300 ℃ at a heating rate of 3 ℃ / min and held for 1 h for heat treatment. Then, the temperature is raised to 1300 ℃ at a heating rate of 8 ℃ / min and held for 3 h for carbonization treatment. After natural cooling to room temperature, the material is taken out and ground into powder to obtain doped hard carbon material.
[0050] S3. Additive Combination: Weigh 1 g of undoped hard carbon material and 3 g of urea, place them in the zirconium oxide ball mill jar of a planetary ball mill, add 30 mL of anhydrous ethanol as the dispersion medium, set the ball-to-material ratio to 10:1, and the ball milling speed to 300 r·min. -1 The mixture was continuously ball-milled for 4 hours to obtain a uniform slurry. The slurry was then poured into an evaporating dish and dried in a 60 °C oven for 12 hours to completely remove anhydrous ethanol, yielding a black powdery composite material.
[0051] S4. Secondary carbonization treatment: Place the black powdered composite material into a tube furnace, and introduce argon gas as a protective atmosphere (gas flow rate 80 mL / min). -1 First, the temperature is increased to 300 ℃ at a heating rate of 3 ℃ / min and held for 1 h for heat treatment. Then, the temperature is increased to 1300 ℃ at a heating rate of 8 ℃ / min and held for 3 h for carbonization treatment. After natural cooling to room temperature, the material is taken out and ground into powder to obtain hard carbon anode material.
[0052] Comparative Example 3 (using corn cob as hard carbon precursor and boric acid as dopant additive) A method for preparing a hard carbon anode material includes the following steps: S1. Hard Carbon Precursor Treatment: After removing mud, sand, outer skin, and visible impurities from the corn cob raw material, it is cut into small pieces and crushed in a pulverizer to obtain coarse corn cob powder. The coarse corn cob powder is sieved through a standard sieve to collect corn cob powder with a particle size of 200 mesh. The sieved corn cob powder is repeatedly washed with deionized water until the washing liquid is clear to remove surface dust and water-soluble impurities. Subsequently, the washed corn cob powder is filtered and dried in an oven at 80 ℃ to obtain pre-treated corn cob powder. 20 g of the pre-treated corn cob powder is weighed and placed in a tube furnace. Under an inert atmosphere, the temperature is increased to 300 ℃ at 8 ℃ / min and held for 3 h for pre-carbonization treatment to obtain pre-carbonized corn cob carbon powder. The obtained pre-carbonized corn cob carbon powder is placed in a mixed acid of 3 mol / L HCl and 5 wt% HF and stirred at 80 ℃ for 12 h to remove silicon impurities and metal ion impurities. The mixture was then washed with deionized water until neutral and dried to obtain black pretreated corn cob toner.
[0053] S2. Additive Combination: Weigh 1 g of black pretreated corn cob carbon powder and 3 g of boric acid, place them in the zirconia ball mill jar of a planetary ball mill, add 30 mL of anhydrous ethanol as the dispersion medium, set the ball-to-material ratio to 10:1, and the ball milling speed to 300 r·min. -1 The mixture was continuously ball-milled for 4 hours to obtain a uniform slurry. The slurry was then poured into an evaporating dish and dried in a 60 °C oven for 12 hours to completely remove anhydrous ethanol, yielding a black powdery composite material.
[0054] S3. Carbonization treatment: The black powdered composite material is placed in a tube furnace, and argon gas is introduced as a protective atmosphere (gas flow rate 80 mL / min). -1 First, the temperature is increased to 300 ℃ at a heating rate of 3 ℃ / min and held for 1 h for heat treatment. Then, the temperature is increased to 1300 ℃ at a heating rate of 8 ℃ / min and held for 3 h for carbonization treatment. After natural cooling to room temperature, the material is taken out and ground into powder to obtain hard carbon anode material.
[0055] Comparative Example 4 (using corn cob as hard carbon precursor and urea as additive). A method for preparing a hard carbon anode material includes the following steps: S1. Hard Carbon Precursor Treatment: Weigh 20 g of corn cob powder obtained after crushing, sieving, washing, and drying. Place it in a tube furnace and pre-carbonize it at 300 °C at 8 °C / min under an inert atmosphere for 3 h to obtain pre-carbonized corn cob carbon powder. Place the obtained pre-carbonized corn cob carbon powder in a mixed acid solution of 3 mol / L HCl and 5 wt% HF and stir at 80 °C for 12 h to remove silicon impurities and metal ion impurities. Then wash with deionized water until neutral and dry to obtain black pre-treated corn cob carbon powder.
[0056] S2. Additive compounding: Weigh 1 g of black pretreated corn cob carbon powder and 3 g of urea, place them in the zirconium oxide ball mill jar of a planetary ball mill, add 30 mL of anhydrous ethanol as the dispersion medium, set the ball-to-material ratio to 10:1, and the ball milling speed to 300 r·min. -1 The mixture was continuously ball-milled for 4 hours to obtain a uniform slurry. The slurry was then poured into an evaporating dish and dried in a 60 °C oven for 12 hours to completely remove anhydrous ethanol, yielding a black powdery composite precursor.
[0057] S3. Carbonization treatment: The black powdered composite precursor is placed in a tube furnace, and argon gas is introduced as a protective atmosphere (gas flow rate 80 mL / min). -1 The temperature was increased to 1300 ℃ at 8 ℃ / min, held for 3 h, and then naturally cooled to room temperature. After being removed, it was ground into powder to obtain hard carbon anode material.
[0058] Comparative Example 5 (using corn cob as hard carbon precursor and urea as additive). A method for preparing a hard carbon anode material includes the following steps: S1. Hard Carbon Precursor Treatment: Weigh 20 g of corn cob powder obtained after crushing, sieving, washing, and drying. Place it in a tube furnace and pre-carbonize it at 300 °C at 8 °C / min under an inert atmosphere for 3 h to obtain pre-carbonized corn cob carbon powder. Place the obtained pre-carbonized corn cob carbon powder in a mixed acid solution of 3 mol / L HCl and 5 wt% HF and stir at 80 °C for 12 h to remove silicon impurities and metal ion impurities. Then wash with deionized water until neutral and dry to obtain black pre-treated corn cob carbon powder.
[0059] S2. Additive compounding: Weigh 1 g of black pretreated corn cob carbon powder and 3 g of urea, place them in the zirconium oxide ball mill jar of a planetary ball mill, add 30 mL of anhydrous ethanol as the dispersion medium, set the ball-to-material ratio to 10:1, and the ball milling speed to 300 r·min. -1 The mixture was continuously ball-milled for 4 hours to obtain a uniform slurry. The slurry was then poured into an evaporating dish and dried in a 60 °C oven for 12 hours to completely remove anhydrous ethanol, yielding a black powdery composite precursor.
[0060] S3. Carbonization treatment: The black powdered composite precursor is placed in a tube furnace, and argon gas is introduced as a protective atmosphere (gas flow rate 80 mL / min). -1 First, the temperature is increased to 150 ℃ at a heating rate of 3 ℃ / min and held for 1 h for heat treatment. Then, the temperature is increased to 1300 ℃ at a heating rate of 8 ℃ / min and held for 3 h. After natural cooling to room temperature, the material is removed and ground into powder to obtain hard carbon anode material.
[0061] Comparative Example 6 (using corn cob as hard carbon precursor and urea as additive). A method for preparing a hard carbon anode material includes the following steps: S1. Hard Carbon Precursor Treatment: Weigh 20 g of corn cob powder obtained after crushing, sieving, washing, and drying. Place it in a tube furnace and pre-carbonize it at 300 °C at 8 °C / min under an inert atmosphere for 3 h to obtain pre-carbonized corn cob carbon powder. Place the obtained pre-carbonized corn cob carbon powder in a mixed acid solution of 3 mol / L HCl and 5 wt% HF and stir at 80 °C for 12 h to remove silicon impurities and metal ion impurities. Then wash with deionized water until neutral and dry to obtain black pre-treated corn cob carbon powder.
[0062] S2. Additive compounding: Weigh 1 g of black pretreated corn cob carbon powder and 3 g of urea, place them in the zirconium oxide ball mill jar of a planetary ball mill, add 30 mL of anhydrous ethanol as the dispersion medium, set the ball-to-material ratio to 10:1, and the ball milling speed to 300 r·min. -1 The mixture was continuously ball-milled for 4 hours to obtain a uniform slurry. The slurry was then poured into an evaporating dish and dried in a 60 °C oven for 12 hours to completely remove anhydrous ethanol, yielding a black powdery composite precursor.
[0063] S3. Carbonization treatment: The black powdered composite precursor is placed in a tube furnace, and argon gas is introduced as a protective atmosphere (gas flow rate 80 mL / min). -1 First, the temperature is increased to 500 ℃ at a heating rate of 3 ℃ / min and held for 1 h for heat treatment. Then, the temperature is increased to 1300 ℃ at a heating rate of 8 ℃ / min and held for 3 h. After natural cooling to room temperature, the material is removed and ground into powder to obtain hard carbon anode material.
[0064] Test Example 1 The BET specific surface area of the hard carbon anode materials prepared in Examples 1-5 and Comparative Examples 1-6 was measured using a McMurray Ticco ASAP2460 nitrogen adsorption analyzer at 77 K. The SAXS scattering intensity of the hard carbon anode materials prepared in Example 1 and Comparative Example 1 was measured using an Anton Paar SAXSess MC2 small-angle X-ray scattering spectrometer. Surface elemental analysis of the hard carbon anode materials prepared in Example 1 and Comparative Example 1 was performed using X-ray photoelectron spectroscopy. The test results are as follows: Figure 1-2 As shown in Table 1: Table 1
[0065] As can be seen from the test data in Table 1, the present invention introduces doping additives before high-temperature carbonization, allowing the doping additives to undergo in-situ pyrolysis and release a large amount of gas at the appropriate timing and temperature window of the carbon matrix's thermal evolution. After subsequent high-temperature carbon layer rearrangement and pore sealing, the BET specific surface area of the resulting hard carbon anode material is significantly reduced, while the SAXS scattering intensity is significantly improved. Figure 1 As shown, BET represents the specific surface area of open channels that can communicate with the outside world. A decrease in BET value indicates a reduction in the number of open pores in the material. SAXS can detect all internal nanopores, including closed pores. An increase in SAXS scattering intensity proves that abundant closed and semi-closed pore structures have been formed inside the material. This confirms that by relying on an appropriate heat treatment temperature window, in-situ gas generation and pore creation with doped additives followed by high-temperature pore sealing can achieve the structural control effect of transforming open pores into internal closed pores.
[0066] Further integration Figure 2Analysis of the XPS images showed that the hard carbon anode material prepared in Example 1 only exhibited obvious C 1s and O 1s characteristic signals, with almost no N 1s characteristic peak; while the hard carbon anode material prepared in Example 1 showed a clearly identifiable N 1s characteristic peak in addition to the C 1s and O 1s signals. This result demonstrates that by introducing doping additives before carbonization and then heat-treating, nitrogen heterogeneous elements were successfully introduced into the hard carbon material, achieving heterogeneous element doping of the carbon framework.
[0067] Test Example 2 The hard carbon anode materials prepared in Examples 1-5 and Comparative Examples 1-6 were used as anode active materials. The anode active material, conductive agent Super P, binder sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) were weighed in a mass ratio of 90:5:1.5:3.5. After shaking and mixing, a small amount of deionized water was added and stirred until homogeneous to obtain a black slurry. The black slurry was coated onto the surface of a copper foil current collector, dried, and then cut into hard carbon electrode sheets with a diameter of 13 mm. A CR2032 button-type sodium-ion half-cell was assembled in a glove box filled with argon atmosphere, using metallic sodium foil as the anode, the aforementioned hard carbon electrode sheet as the positive electrode, a 1 M sodium hexafluorophosphate (NaPF6) / diethylene glycol dimethyl ether solution as the electrolyte, and glass fiber as the separator.
[0068] The assembled sodium-ion half-cell was subjected to constant current charge-discharge tests using a LAND-CT3004A testing system, within the range of 0-2.5 V (vs. Na). + Charge-discharge tests were conducted at a voltage range of / Na and a current density of 20 mA / g. The test results are as follows: Figure 3 As shown in Table 2: Table 2
[0069] Depend on Figure 3 As can be seen from the test data in Table 2, compared with Comparative Example 1, Examples 1-5 all introduced doping additives before carbonization treatment, and the reversible sodium storage capacity, plateau capacity ratio and first coulombic efficiency of the resulting hard carbon anode materials were significantly improved.
[0070] Examples 1-3 used the same corn cob precursor and selected urea, thiourea, and ammonium borate as doping additives, respectively, all of which achieved high reversible sodium storage capacity and plateau capacity ratio. Examples 1, 4, and 5 used corn cob, coconut shell, and bamboo powder as hard carbon precursors, respectively, and selected urea as a doping additive. The resulting materials all exhibited excellent sodium storage performance, confirming that the technical solution of the present invention has wide applicability to various precursors. Among them, Example 1, which used corn cob as a hard carbon precursor, showed the best overall performance.
[0071] Comparing Example 1 and Comparative Example 2, both used the same carbon precursor and dopant additives, only changing the timing of the dopant additive composite. Comparative Example 2, after carbonization, underwent a second heat treatment with urea, resulting in a limited increase in reversible sodium storage capacity and a significant decrease in the plateau capacity ratio. This is because the carbon matrix had already been carbonized and solidified, making it difficult for the gas generated by the pyrolysis of the dopant additives to construct closed-pore structures within the carbon material. Furthermore, heterogeneous elements were difficult to effectively incorporate into the carbon framework, failing to achieve the synergistic control of pore formation and doping. This demonstrates that completing the composite of the dopant additives before carbonization is a necessary condition for obtaining high plateau capacity hard carbon materials.
[0072] Comparing Example 1 and Comparative Example 3, the precursors, recombination timing, and heat treatment processes were completely identical, with the only difference being the replacement of the doping additive with boric acid, which has weak gas-generating capacity. The reversible sodium storage capacity, plateau capacity ratio, and initial coulombic efficiency of Comparative Example 3 were significantly lower than those of Example 1. Although boric acid can achieve elemental doping, the amount of gas released during pyrolysis is small, failing to generate sufficient closed / semi-closed pore sodium storage sites. This confirms that the doping additive needs to simultaneously possess the dual functions of pyrolysis gas generation and providing heteroatoms; additives that only provide heteroatoms cannot achieve the electrochemical performance expected by this invention.
[0073] Comparative Examples 4, 5, and 6 were compared with Example 1. The hard carbon precursor, dopant, and timing of dopant compounding were all consistent, with only the carbonization heat treatment process differing. Electrochemical test results showed that the reversible sodium storage capacity, plateau capacity ratio, and initial coulombic efficiency of the three comparative examples were significantly lower than those of Example 1. Comparative Example 4 employed a rapid heating one-step pyrolysis process, where the dopant rapidly and violently decomposed in a short time, generating a large amount of gas instantaneously, causing severe foaming of the matrix. This easily led to pore structure collapse and particle breakage, making it difficult to construct sufficient and stable closed / semi-closed pore sodium storage sites within the carbon matrix, resulting in the lowest plateau capacity ratio. Comparative Examples 5 and 6, although employing the same two-step pyrolysis mode as Example 1, had first-stage heat treatment temperatures deviating from the optimal temperature window. The first-stage heat treatment temperature of Comparative Example 5 was too low, resulting in insufficient decomposition and activation of the dopant, and insufficient total in-situ gas generation. During the high-temperature stage, the residual additives rapidly decomposed, causing severe local foaming, ultimately forming an unevenly distributed pore structure with fewer effective storage sites. In Comparative Example 6, the first stage heat treatment temperature was too high, resulting in an excessively rapid pyrolysis rate of the additives and overly intense gas release. This easily led to the formation of numerous large pores and interconnected open pores within the carbon matrix, making it difficult to generate a uniform and dense microporous structure. Consequently, the pores could not effectively close during the subsequent high-temperature rearrangement process, hindering the formation of closed / semi-closed pore structures with high sodium storage capacity. These results confirm that the two-step heat treatment process plays a crucial role in inducing the formation of closed-pore structures within the carbon matrix.
[0074] In summary, this invention uses biomass raw materials such as corn cobs, coconut shells, and bamboo powder as hard carbon precursors, and selects urea, thiourea, and ammonium borate as doping additives. A closed-pore enrichment type in-situ gas-assisted pore-forming and doped hard carbon anode material is prepared through pre-carbonization, ball milling, and segmented high-temperature carbonization under an inert atmosphere. This invention constructs a synergistic control mechanism of "in-situ gas release - pore structure formation - heteroelement doping - high-temperature carbon layer rearrangement and pore sealing - plateau capacity improvement." By combining the carbon precursor with gas-release doping additives and simultaneously completing in-situ pore-forming, elemental doping, and high-temperature pore sealing through segmented heat treatment, it can optimize the pore structure of hard carbon and introduce heteroelement doping to regulate the structure, significantly improving the sodium storage capacity and first coulombic efficiency of the material. The process is simple and easily scalable.
[0075] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art should understand that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a hard carbon anode material, characterized in that, Includes the following steps: S1. Hard carbon precursor powder is obtained by crushing, sieving, washing and drying the hard carbon precursor. The hard carbon precursor powder is pre-carbonized at 200-400 °C and then acid-washed to remove impurities to obtain pre-treated hard carbon precursor. S2. The pretreated hard carbon precursor obtained in step S1 is uniformly mixed with the doping additive to obtain a composite precursor; the doping additive is selected from one or more of urea, thiourea, ammonium borate, ammonium phosphate, melamine, dicyandiamide, cyanamide, ammonium oxalate, ammonium bicarbonate, amino acids and chitosan. S3. Under an inert atmosphere, the composite precursor obtained in step S2 is first heat-treated at 200-400 °C to allow the doped additives to release gases through thermal decomposition, and then carbonized at 800-1600 °C to obtain the hard carbon anode material.
2. The preparation method according to claim 1, characterized in that, In step S1, the hard carbon precursor is selected from one or more of the following: corn cob, coconut shell, bamboo powder, rice husk, walnut shell, waste tea leaves, coffee grounds, apple peel, banana peel, lignin, cellulose, starch, glucose, sucrose, and fructose.
3. The preparation method according to claim 1, characterized in that, In step S1, the specific operation of the pre-carbonization treatment is as follows: the hard carbon precursor powder is placed in a tube furnace and heated to 200-400 ℃ at a heating rate of 5-10 ℃ / min under an inert atmosphere, and held at that temperature for 1-48 h for pre-carbonization treatment.
4. The preparation method according to claim 1, characterized in that, In step S1, the acid washing and impurity removal treatment uses one or more of hydrochloric acid, nitric acid, hydrofluoric acid, sulfuric acid, oxalic acid and citric acid.
5. The preparation method according to claim 1, characterized in that, In step S1, the acid washing and impurity removal process takes 1-12 hours.
6. The preparation method according to claim 1, characterized in that, In step S2, the mass ratio of the pretreated hard carbon precursor to the doped additive is 1:(1-10).
7. The preparation method according to claim 1, characterized in that, In step S2, the mixing method is grinding or ball milling.
8. The preparation method according to claim 1, characterized in that, In step S3, the composite precursor is placed in a tube furnace and heated to 200-400 ℃ at a heating rate of 1-5 ℃ / min under an inert atmosphere, and held at that temperature for 1-5 h for heat treatment. Then, it is heated to 800-1600 ℃ at a heating rate of 5-10 ℃ / min and held at that temperature for 1-48 h for carbonization treatment.
9. A hard carbon anode material prepared by the preparation method according to any one of claims 1-8.
10. The application of the hard carbon anode material according to claim 9 in a sodium-ion battery.